Endocrine disruptors in boiled drinking water carried in plastic containers: a pilot study in Thrissur, Kerala, India - T. Geetha (SpringerOpen, 2021)
Abstract Boiled drinking water is carried by students to schools and colleges in plastic containers. However, the risk associated with drinking water stored in plastic containers is very real especially the question of leachates finding their way into the water stored in these containers. In this pilot study, we identified the most common plastic container used by students to carry water and the factors that govern their choice. Polyethylene terephthalate (PET) was identified as the most favored plastic used to carry water. PET bottles were then subject to treatments that mimic conditions representative of normal consumer usage. The water sample collected was tested for the presence of phthalates, antimony & titanium, and their content estimated by gas chromatography and atomic absorption spectra. Although phthalates and antimony leach into water from PET bottles their concentration was not high enough to pose a threat to human life. However, the trend of increasing antimony concentration with temperature and time is a cause of concern because of its role as endocrine disruptors. Prolonged and repeated use of PET bottles to carry water, especially warm water may lead to health problems in the community.